A novel approach of remotely calibrating the active phased array antenna using PNA. (10th September 2019) - Syed, Momina; Mahalingam, M. Sandhana; Ramanjaneyulu, B. Seetha
This paper presents a novel approach of remotely calibrating the active phased array antenna using Pulse Network Analyser (PNA). Phased array antennas are usually calibrated at the factory using near-field range calibration. However, when these antennas are used in the field, due to the presence of solid state components, their characteristics may change over time. Owing to these changes, the requirement arises to recalibrate the array in the field. Calibration is necessary to know the element-wise transmitting power, receiver gain, attenuation, element failures and characteristics of phase shifters. A proper calibration will ensure desired antenna pattern and system accuracy. In this work, a technique that is suitable for calibration in both transmit and receive paths of phased array antenna using far-field method, is developed. A suitable setup was established for implementing the above technique using the PNA. Remote control of the setup was done using Matlab software. Results obtained indicate the successful calibration of the system.